Makna Rasa Syukur dalam Film “Cinta Tapi Diam” Produksi Film Maker Muslim Episode 5: (Analisis Narasi Tzvetan Todorov) - Annisa Farhatul Jannah; Ahmad Rofi’Syamsuri; Sofyan Rizal (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
In such a modern era like now, many Muslims use social media as a means to preach, one of which is through film media, film is media communication which presents sound and images. much praise from the audience. This film provides an overview of gratitude and an unyielding attitude in living life regardless of the circumstances From the description above, the problem formulation is as follows: What is the meaning of gratitude in the film Cinta Tapi Diam on the Youtube channel Film Maker Muslim – FMM Studios episode 5 in an Islamic perspective? This study aims to find out the meaning of gratitude in the film Cinta Tapi Diam on the Youtube channel Film Maker Muslim – FMM Studios episode 5 in an Islamic perspective so that it can be an example that can be learned from. The type of research used is descriptive qualitative research, with data collection techniques in the form of documentation. This research uses the Tzvetan Todorov narrative analysis method which consists of 3 stages, namely the initial stage which is the preliminary stage, where the middle stage where disturbance or conflict begins and the final stage is is the stage of solving the problem or the occurrence of a solution. The results of this study found that many scenes and dialogues contain the meaning of gratitude both directly and indirectly.